PEMBIMBINGAN JEMAAT DI GEREJA KRISTEN OIKOUMENE RIMBA BELIAN TENTANG REVITALISASI PEMAHAMAN PERNIKAHAN KUDUS - Hia, Yeremia (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2024)
Holy marriage is an essential concept in Christian teachings, yet its understanding is often neglected by the congregation. At GKO Rimba Belian, revitalizing the understanding of holy marriage has become a significant focus in strengthening the moral and spiritual integrity of the congregation. The primary challenge faced is the lack of awareness regarding the importance of a God-blessed marriage and the ethical values contained in the Bible, as referenced in Hebrews 13:4 and Genesis 1:27-31. This research aims to guide the congregation in understanding marriage as a sacred institution that involves moral responsibility, reason, and love, as outlined in Colossians 3:14. Utilizing a participatory method that incorporates discussions, Bible studies, and direct mentorship, this research offers a comprehensive approach to educating the congregation. The uniqueness of this study lies in the integration of spiritual guidance and theological understanding of marriage, a combination rarely applied in church contexts. The results demonstrate an increased understanding of holy marriage among the congregation and a strengthened commitment to these values.